Broadening the design space of engineering materials through “additive grain boundary engineering” - Seita, Matteo (2022)
Grain boundary engineering (GBE) is one of the most successful processing strategies to improve the properties of polycrystalline solids. However, the extensive thermomechanical processes involved during GBE restrict its use to selected applications and materials. In this viewpoint paper, we discuss the opportunity provided by additive manufacturing (AM) technology to broaden the applicability of the GBE paradigm and, consequently, the design space for engineering materials. By integrating specially-designed thermomechanical processing within AM, it would be possible to produce bulk, near-net-shape parts with complex geometry and GBE microstructure. We discuss the major challenges in this endeavor and propose some possible strategies to achieve this goal, which we refer to as “additive-GBE”.